Introduction: Future-proof Regulation and Enforcement for the Digitalised Age - Gavin Robinson; Sybe de Vries; Bram Duivenvoorde (European Papers, 2023)
(Series Information) European Papers - A Journal on Law and Integration, 2023 8(2), 579-582 | Article | (Abstract) This Special Section is devoted to assessing whether core areas and core values of European law are future-proof (and how they could or should be made future-proof) in light of developments in terms of digitalisation and technological innovation. It is the result of a joint project of researchers at the Utrecht Centre for Regulation and Enforcement in Europe (RENFORCE) at Utrecht University, focusing on the impact of digitalisation in different fields of EU law including EU internal market law, consumer protection law, data protection law, competition law, financial law, intellectual property law and criminal law. Digital technologies create various challenges, in many cases associated with the use of algorithms, the massive collection of personal data and the possibilities (and difficulties) of access to digital content. All these challenges require careful consideration, and regulation and enforcement arrangements which protect and balance the possibly conflicting values that we deem important in our societies, including innovation and technological development and protection of fundamental rights. Yet, it is exactly the continuous and fast-paced technological developments that make it difficult to regulate in these areas. In the EU, this response is predominantly shaped and guided within the multi-level legal order, whereby the EU legislature has gained a growing role in shaping our digital societies. The Special Section editors hope that the contributions provide food for thought, useful insights and inspiration for the process of making regulation and enforcement in the EU (more) future-proof for digitalisation – both within the specific fields of expertise and beyond.